REORIENTASI KURIKULUM PENDIDIKAN AGAMA ISLAM BERBASIS HUMANISME TEOSENTRIS - Masruroh; Hadi, Syaiful (Almarhalah: Jurnal Pendidikan Islam, 2026)
This study aims to analyze the reorientation of the Islamic Religious Education (PAI) curriculum based on the concept of theocentric humanism as an approach to strengthening students’ holistic, balanced, and value-oriented character formation. Theocentric humanism is understood as an educational paradigm that positions humans as active subjects of learning while grounding the entire educational process in divine values derived from Islamic teachings. This study employs a qualitative literature-based method by examining books, scholarly articles, policy documents, and recent studies related to curriculum development and humanistic perspectives in Islamic education. The research findings reveal three major points. First, the current PAI curriculum often experiences a reduction in meaning due to its dominant focus on cognitive and formalistic aspects, which results in limited attention to existential, emotional, and humanistic dimensions of students’ development. Second, the paradigm of theocentric humanism provides a philosophical framework that harmonizes human dignity with divine principles, making it highly relevant as the foundation for reorienting the PAI curriculum. Third, implementing a theocentric-humanist curriculum requires reformulation of learning objectives, reconstruction of materials, integration of Qur’anic humanistic values, and transformation of the teacher’s role into a moral and spiritual mentor. The study concludes that reorienting the PAI curriculum toward theocentric humanism is an urgent necessity to create a more relevant, moderate, and transformative educational process aimed at shaping holistic Islamic personalities. Such reorientation has the potential to strengthen students’ character, deepen spirituality, and foster social consciousness grounded in divine guidance.